2010
DOI: 10.1111/j.1462-5822.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

The fungal pathogen Cochliobolus heterostrophus responds to maize phenolics: novel small molecule signals in a plant-fungal interaction

Abstract: SummaryThe transcription factor ChAP1 of the fungal pathogen of maize, Cochliobolus heterostrophus, responds to oxidative stress by migration to the nucleus and activation of antioxidant genes. Phenolic and related compounds found naturally in the host also trigger nuclear localization of ChAP1, but only slight upregulation of some antioxidant genes. ChAP1 thus senses phenolic compounds without triggering a strong antioxidant response. We therefore searched for genes whose expression is regulated by phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…On the other hand, the low efficiency of T. flavus bioformulation containing magnesium sulfate in certain pathogenic agents could be due to the incompatibility of T. flavus antagonist with the mentioned compounds. The studies of Hiscox et al (2015) and Shanmugam et al (2010) in this regard showed that it is considered as stress for fungal growth under certain chemical conditions. It is supposed that it happens before T. flavus bioformulation enters the soil, though magnesium compounds in certain cases caused the weak growth of T. flavus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the low efficiency of T. flavus bioformulation containing magnesium sulfate in certain pathogenic agents could be due to the incompatibility of T. flavus antagonist with the mentioned compounds. The studies of Hiscox et al (2015) and Shanmugam et al (2010) in this regard showed that it is considered as stress for fungal growth under certain chemical conditions. It is supposed that it happens before T. flavus bioformulation enters the soil, though magnesium compounds in certain cases caused the weak growth of T. flavus.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of detoxification pathways upon contact with plant antifungal defenses has been reported for other phytopathogenic fungi. Among phenolic compounds, caffeic acid induces the transcription of a gene cluster involved in the b-ketoadipate pathway in Cochliobolus heterostrophus, the causal agent of southern corn leaf blight (Shanmugam et al, 2010), while phenolic compounds and pectin induce laccases responsible for stilbene dimerization in B. cinerea (Gigi et al, 1980). However, not all detoxification pathways are inducible.…”
Section: Discussionmentioning
confidence: 99%
“…However, wounding of seedlings should generate a burst of ROS and a state of oxidative stress for hyphae inoculated at the wound site (56,57). Wounding may also result in a release of phenolics that have been shown to induce relocalization of GFP-ChAP1 to the nucleus in Cochliobolus heterostrophus (68). Using YapA-EGFP as a redox sensor, we were able to show that YapA-EGFP hyphae in direct contact with the wound, as well as in cells more distant from the wound site, relocalized to the nucleus within 30 min of wounding.…”
Section: Figmentioning
confidence: 99%